NEWSROOMS AS NON PLACES - Reyna, Víctor Hugo (Brazilian journalism research, 2021)
ABSTRACT – The objective of this article is to analyze the meaning of journalists’ voluntary turnover in the configuration of the space that they have historically occupied: newsrooms. Drawing on Auge’s concept of non-place and fieldwork in the leading newspapers of three northern Mexican states, it is discovered that the recurring recreation of turnover events transforms newsrooms from spaces of permanence into spaces of transition; that is, from places to non-places. The scope of this phenomenon transcends the entry and exit of a certain generation since it erodes the identitarian, relational and historical character of these spaces. RESUMO – O objetivo deste artigo é analisar o significado da rotatividade voluntária dos jornalistas na configuração do espaço que historicamente ocuparam: as redações. Com base no conceito de Augé de não-lugar e do trabalho de campo realizado junto aos principais jornais de três estados do norte do México, conclui-se que a recorrência de eventos de demissão transforma as redações, de espaços de permanência em espaços de transição; ou seja, de lugares em não-lugares. O alcance deste fenômeno transcende a entrada e saída de uma determinada geração, pois corrói a identidade, o carácter relacional e histórico destes espaços. RESUMEN – El objetivo de este artículo es analizar el significado de la rotación de personal voluntaria de los periodistas en la configuración del espacio que históricamente han ocupado: las salas de redacción. A partir del concepto de no lugar de Augé y trabajo de campo en los principales periódicos de tres estados del norte de México, se descubre que la recreación recurrente de los eventos de renuncia transforma a las redacciones de espacios de permanencia en espacios de transición; es decir, de lugares en no lugares. El alcance de este fenómeno trasciende la entrada y la salida de determinada generación, pues erosiona el carácter identitario, relacional e histórico de estos espacios.